Evaluation of Bilingual Intercultural Approach in Indigenous Primary Education: Case Study in the Indigenous Region Los Altos, Chiapas - Viveros-Márquez, José (2016)
The objective of this study was to evaluate the implementation of the EIB (Bilingual Intercultural approach, by its acronym in Spanish) in an elementary indigenous school located in San Cristóbal de las Casas, Chiapas. This school is characterized by the cultural and linguistic diversity represented by the integration of teachers, students and parents of tseltal and tsotsil origin. We use the evaluation model CIPP (context, input, process and product) and complemented it with school ethnography, using semi-structured interviews (director and supervisor), participant observation (classroom sessions), focus group interviews to teachers and parents and a sociolinguistic questionnaire to students. The theoretical framework retrieves the core theoretical elements of the EIB, by reviewing and analysing bilingual education, bilingual bicultural education (biculturalism), pedagogical interculturalism and the intercultural bilingual approach. The main findings of this study show that, in practice, intercultural bilingual indigenous education has not transcended the bilingual dimension (the indigenous language teaching). Interculturalism is not yet clearly integrated in the speech nor in the educational practice of the studied school. The EIB implementation is still limited and responds to sociocultural, linguistic, political, educational and teacher training conditions that characterize the local educational context and are not favorable to enhance the effective implementation of the EIB in the primary school.